Bioinspired interfacial design for gravity-independent fluid transport control. (June 2022) - Liu, Jing; Cao, Min; Li, Long; Xu, Xue; Zheng, Jing; Yao, Wei; Hou, Xu
Abstract: In nature, numerous creatures have evolved exquisite structures, surface wettabilities, and interfacial interactions to manipulate fluids for survival, such as water collection, water feeding, air capture, air exchange, etc . These unique functionalities have become a constant source of inspiration for human beings to explore versatile applications. Recently, the control of gas or liquid transport has attracted more and more attention owing to the great potentiality in various fields. Particularly, the drive that does not rely on gravity is of great significance for applications under micro- or reduced-gravity conditions. This review gives a brief description of the fluid transport control mechanisms in living organisms and the biomimetic interfacial design to create controllable fluid manipulation devices. The recent progress of gravity-independent liquid transport, underwater gas transport, and multiphase fluids transport are classified and summarized. The crucial influence of geometric structures and interfacial wettabilities on fluid dynamic behaviors and the driven mechanisms behind these behaviors, along with emerging applications, opportunities, and challenges, are presented. Graphical abstract: Image, graphical abstract